The Effect of Jigsaw Type of Cooperative Learning Model on Concepts Understanding and Critical Thinking Skills of Students in Class V SD Negeri 112146 Janji in the Science Lesson, Academic Year 2021/2022 - Aland Wijaya Kusuma; Adi Sutopo; Benny Agus Pribadi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2022)
This study aims: (1) To determine the level of students' conceptual understanding after jigsaw type cooperative learning. (2) To determine the level of students' thinking ability after jigsaw type cooperative learning. (3) To determine the effect of jigsaw type learning method on concept understanding ability. (4) To determine the effect of the jigsaw learning method on critical thinking skills. The type of experimental research used is Quasi-Experimental. The research subjects consisted of 80 students. Samples were taken from the subject population consisting of 40 students in class V a (control group) and 40 students in class V b (experimental group). The results showed that the jigsaw method significantly affected the understanding of concepts and thinking skills of the fifth grade students of SDN 112146 Janji in social studies subjects. The activity of understanding the concept and thinking skills of the experimental class students reached very high criteria, while in the control class it only reached the sufficient criteria. The average posttest score of the experimental group was better than the control group. The mean posttest of the experimental group was 74.13 and the mean posttest of the control group was 66.23. This shows that the gain index <g> of the experimental group is 73.45 (high) while the <g> of the control group is 65.62 (medium). The results of the t-test show that the value of tcount (2,272) > ttable (1,990) means that the Jigsaw method has an effect on social studies learning outcomes and the value of Sig. (2-tailed) < 0.05 that is 0.026. These results conclude that there is a significant difference between the learning outcomes of the experimental class and the control class.